Use of Lévy's Model to Simulate Stock Dividends Actual Estimations of some Iraqi Banks - Hamood, Munaf Youssuf; Moossa, Mariyam Jum'a (International Journal of Psychosocial Rehabilitation, 2020)
In this study, one of the models of random contingent processes was studied, which is one of the Lévy models, based on the Brownian subordinate. It was relied on the so-called Normal Inverse Gaussian (NIG). This study aims at estimating the parameters of this model using the moments and maximum likelihood methods and then employing these estimations for the parameters in studying stock dividends and knowing the market efficiency of both the United Bank and the North Bank whose data were collected from Iraq Stock Exchange. As well as the use of simulation method to simulate the applied side with the different assumed cases. The simulation results also indicated that the increasing value of kurtosis parameter and the decreasing skewness parameter in the NIG model resulted in a decrease in the large fluctuations, especially when increasing the sizes of the samples. The decrease in volatility parameter was better than its increase for the North Bank, unlike the United Bank, where the increase of volatility had an impact on the reduction of the MASE.